Sensory profiles and seasonal variation of black walnut cultivars and the relationship between sensory characteristics and consumer acceptance of black walnut gelato - Lynch, Catherine A. (Catherine Anne) (Kansas State University, 2015)
Black walnut (Juglans nigra L.) is a Juglans species native to the United States. Nuts are collected each fall from black walnut trees and the kernels are consumed in many food products like ice cream, candies, and baked goods. Flavor profiles of black walnut cultivars have been examined, but no studies have looked at the effect of growing season on flavor profile, and few studies have determined consumer acceptance of black walnut food products. The sensory profiles of 10 black walnut cultivars (Football, Vandersloot, Brown Nugget, Pounds, Sparks 127, Davidson, Sparrow, Neel, Emma K, and Tomboy) were evaluated using descriptive sensory analysis. A trained panel scored the intensity of 3 appearance, 7 aroma, 23 flavor, and 6 texture attributes. Results showed that the cultivars differed significantly (P≤0.05) on 11 of these attributes. The results from this study were also compared to results collected in 2011 of 7 black walnut cultivars. Two flavor attributes (black walnut ID and overall nutty) had an interaction effect of year and cultivar, while 7 attributes showed a main effect of year (brown, caramelized, floral/fruity, fruity,-dark piney, musty/dusty, and oily). In general, flavor attributes had higher intensities in 2011 than in 2013. Six of the black walnut cultivars were also incorporated into a gelato base and evaluated by both a trained panel and consumer panel. Trained panelists developed a lexicon for the gelato samples and scored the intensity of 18 flavor attributes. The gelato samples differed on 3 main flavor attributes: black walnut ID, overall nutty, and sour (P≤0.05). Based on consumer liking, there were 3 distinct clusters of consumers. One cluster preferred samples with a milder black walnut flavor, another preferred a more intense black walnut and overall nutty flavor, and the third cluster liked all of the samples. Results from this study indicate that growing season should be considered when determining flavor profile of agricultural products. These results can also help guide growers in selecting cultivars that may produce a more consistent crop year after year, and cultivars that consumers find acceptable in food products.
Keywords: Sensory; Consumer acceptance; Black walnut; Seasonal variation; Food Science (0359)